The Marketplace of the Heart: Penance and Redemption in the Wings of the Mérode Triptych - Padgett Lea, Patricia (De Medio Aevo, 2026)
Visual exegesis of the Annunciation Triptych’s figurative wordplay calls for a reassessment of Robert Campin’s fundamental importance to early Netherlandish Art. During the first quarter of the fifteenth century, when treatises on the art of memory began to proliferate in Southern and Central Europe, similar manuals were relatively rare in the Low Countries, where the locations (loci) and vivid images (imagines agentes) of mendicant rhetoric had become the memory prompts in devotional paintings that guided penitents on their journey to God. Following a spiritual guide through a door is an immersive sensory experience quite different from viewing the world through a picture window. The former is medieval, the latter, early modern. When Campin decided to replace the gold of eternity with blue sky and white clouds in Mary’s bourgeoise living room, he sited the Virgin’s solar at the top of the stairs, high above the courtyard of conscience and the workshop of redemption in the triptych’s respective wings. These locations and images — which follow the rhetorical rules of similarity, dissimilarity and contiguity — prompted the male votary to remember, confess and expiate his sins as he moved through the classic stages of spiritual ascent — purification in the left wing, illumination in the right wing and union in the central panel